Electrochemical deposition of Fe–Mo–W alloy coatings from citrate electrolyte - Karakurkchi, A. V.; Ved, M. V.; Yermolenko, I. Yu.; Sakhnenko, N. D. (Allerton Press, 2016)
Peculiarities of the electrochemical deposition of Fe–Mo–W coatings from citrate electrolyte containing iron (III) on the substrates of mild steel and gray cast iron are investigated. The effect of the salt concentration of alloying components and electrolysis modes on the quality, composition, and properties of the alloys is determined. It is shown that the alloys formed via nonstationary electrolysis exhibit a more uniform surface and lower content of impurities. The improved physical and mechanical properties as well as corrosion resistance of Fe–Mo–W coatings in comparison with the base metal can be considered as promising technologies for surface hardening and repair of worn items.

Исследованы особенности электрохимического формирования покрытий Fe-Mo-W из цитратного электролита на основе железа (III) на подложках из малоуглеродистой стали и серого чугуна. Установлено влияние концентрации солей сплавообразующих компонентов и режимов электролиза на качество, состав и свойства полученных сплавов. Показано, что сплавы, сформированные в условиях нестационарного электролиза, имеют более равномерную поверхность и характеризуются меньшим содержанием примесей. Повышенные физико-механические и антикоррозионные свойства покрытий Fe-Mo-W в сравнении с основным металлом позволяют рассматривать их как перспективные в технологиях упрочнения поверхностей и ремонта изношенных изделий.
Электрохимическое формирование покрытий сплавом Fe-Mo-W из цитратного электролита
Keywords: citrate electrolyte; physical properties; mechanical properties; electrochemical formation; электролит цитратный; свойства физико-механические; формирование электрохимическое